Penguatan Karakter Siswa Melalui Pelatihan Pembuatan Aplikasi Berbasis Mobile di SD Moria Kota Sorong - Melda Agnes Manuhutu; Sherly Gaspersz; Lulu Jola Uktolseja; Irwan Soulisa; Deny Deny; Adika Adika; Wasty Wasty (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This community service activity aims to strengthen the character development of elementary school students through training in creating digital applications using the Thunkable platform. In the midst of the digital era and the challenges of the Industrial Revolution 4.0, character education is an essential aspect that must be instilled from an early age, alongside cognitive competence. Elementary schools, as the foundation of education, play a strategic role in shaping children’s personalities, including embedding positive character values. This activity was conducted at SD Moria in Sorong City and involved 24 students from grades 5 and 6, selected based on their interest and readiness. The training used a Project-Based Learning approach, where students were actively engaged in creating simple application projects. Throughout the process, students not only learned basic programming skills using Thunkable but also developed key values such as teamwork, responsibility, independence, creativity, and curiosity. Despite facing challenges such as limited devices and internet access, the students demonstrated remarkable enthusiasm. Thunkable proved to be an effective tool for interactive and enjoyable learning. Students were able to directly develop their creative ideas through designing user interfaces and application functions. This provided a meaningful learning experience that motivated students to continue exploring and trying new things. The activity showed that technology-based learning can serve as a strategic means to holistically shape students' character. Overall, this initiative demonstrated that digital application development training can serve as a character education model based on technology that is highly relevant for elementary education. This program is expected to serve as an educational innovation example that encourages the integration of digital literacy and character education in Indonesian elementary schools.